Are concepts of achievement-related emotions universal across cultures? A semantic profiling approach. Issue 7 (2nd October 2020) - Loderer, Kristina; Gentsch, Kornelia; Duffy, Melissa C.; Zhu, Mingjing; Xie, Xiyao; Chavarría, Jason A.; Vogl, Elisabeth; Soriano, Cristina; Scherer, Klaus R.; Pekrun, Reinhard
ABSTRACT: Verifying that conceptualisations of emotions are consistent across languages and cultures is a critical precondition for meaningful cross-cultural research on emotional experience. For achievement-related emotions tied to successes or failures, such evidence is virtually non-existent. To address this gap, we compared Canadian, German, Colombian, and Chinese university students' ( N Total = 126) perceptions of affective, cognitive, motivational, physiological, and expressive characteristics of 16 achievement-related emotions using a psycholinguistic tool for profiling emotion concepts (Achievement Emotions CoreGRID). Cross-cultural similarity of emotion concepts quantified through double-entry intraclass correlations was generally high, and highest for their affective, cognitive, and motivational components. However, results also point to cultural variation, particularly for physiological and expressive components. Variation in perceived physiological characteristics was most pronounced for boredom, and for comparisons of Canada, Germany, and Colombia with China. Implications for theoretical propositions of universality of emotion concepts and future research on achievement-related emotions are discussed.